Development of a Method to Obtain More Accurate General and Oral Health Related Information Retrospectively - A, Golkari (J Dent Biomater, 2017)
STATEMENT OF PROBLEM: Early childhood is a crucial period of life as it affects one’s future health. However, precise data on adverse events during this period is usually hard to access or collect, especially in developing countries. OBJECTIVES: This paper first reviews the existing methods for retrospective data collection in health and social sciences, and then introduces a new method/tool for obtaining more accurate general and oral health related information from early childhood retrospectively. MATERIALS AND METHODS: The Early Childhood Events Life-Grid (ECEL) was developed to collect information on the type and time of health-related adverse events during the early years of life, by questioning the parents. The validity of ECEL and the accuracy of information obtained by this method were assessed in a pilot study and in a main study of 30 parents of 8 to 11 year old children from Shiraz (Iran). Responses obtained from parents using the final ECEL were compared with the recorded health insurance documents. RESULTS: There was an almost perfect agreement between the health insurance and ECEL data sets (Kappa value=0.95 and p < 0.001). Interviewees remembered the important events more accurately (100% exact timing match in case of hospitalization). CONCLUSIONS: The Early Childhood Events Life-Grid method proved to be highly accurate when compared with recorded medical documents.